(untitled) (Quest Journal of Management and Social Sciences, 2019)
Background: Although consumers are increasingly concerned with ethical factors when forming product opinions and making purchase decisions, recent studies have highlighted significant differences between consumers’ ethical consumption intentions and their actual buying behavior.Various dimensions concerning how consumers make purchase and consumption decisions and the driving forces behind them have been identified through this study. Objectives: This paper aims to explore the factors leading the gap between attitudes and behavior of consumers in relation to ethical consumption. Methods: The desk review carried out on various related studies reflects that the factors that obstruct the process of ethical consumption and thereby being responsible in forming attitude-behavior gap, which can be helpful in the course of management decision implications worth encouragement of ethical consumption behavior. Moreover, conceptual framework that has been developed for ethical consumption also indicates the factors responsible for creating ethical intention-behavior gap. Findings: This study derives concepts on ethical consumption from literature survey and identifies consumers’ understanding level on ethical consumption. Likewise, the study also provides a comprehensive picture of factors impeding ethical consumption among consumers while providing some theoretical and analytical applications. Conclusions: Price, quality, taste, brand image of products and convenience are some of the considerable issues while buying, due to which consumers’ ethical concerns towards society and environment are not transformed into their consumption behavior.